PENGARUH TEKNOLOGI INFORMASI, PENGETAHUAN INVESTASI DAN MOTIVASI INVESTASI TERHADAP MINAT INVESTASI MAHASISWA - Tia Nur Faridah; Damayanti Damayanti (J-MACC, 2023)
Investment interest is a desire that arises from within a person to learn everything related to investment. The purpose of this study was to see how much influence information technology, investment knowledge and investment motivation had on the investment interest of YPPI Management Study Program students at Rembang University with an active student population of YPPI Management Study Program at Rembang University from Class of 2019 to 2021, totaling 260 and obtaining a sample of 80 student. In selecting the sample of this study using a proportional stratified random sampling technique. With multiple linear regression data analysis techniques. This study found that the variables of information technology and investment motivation had a positive and significant effect on the investment interest of YPPI University Management Study Program students in Rembang. while the investment knowledge variable has a positive but not significant effect on the investment interest of YPPI University Management Study Program students in Rembang. the determination test shows a result of 73.6%, which means that the independent variables (information technology, investment knowledge and investment motivation) can explain the influence of the dependent variable (student investment interest) of 73.6%, while the remaining 26.4% is influenced by factors other than the research model.